Cultura do tomateiro: relação entre o uso de biofertilizante e os danos causados pela traça do tomateiro - Grisa, Simone (2008)
The liquid biofertilizing usage has been one of the used process over pest and sicknesses control and in the plant mineral constitution, specially for tomato culture. On this way, this essay aimed to evaluate Supermagro biofertilizing doses effect over appearance of the tomato plant moth (tuta absoluta). The experiments were conducted in the biological control complex and protected culture Professor Mário Lopes from UNIOESTE Universidade Estadual do Oeste do Paraná, in Marechal Cândido Rondon with latitude of 24º33 S and longitude of 54º04 W and average altitude of 420 meters. The experimental delineation was constituted by casualized blocks with five repetitions, on a factorial scheme 4x5. The first factor is constituted of four ages of plant evaluation: on 30, 63, 86 and 123 days after the transplant and the second out of five biofertilizing levels: 5, 10, 15, 20 and 25 t ha-1 with Supermagro biofertilizing. It was used Italian tomato type seedling cv Saladete, hybrid DRW 3410. The biofertilizing was produced in September 2006 where the process was the continued liquid composite. The experiment was accomplished in a semi-acclimatized greenhouse. The evaluated parameters were: high (cm), diameter (mm), the accumulated number of caterpillar of T. absoluta, the percentage of attached fruit by T. absoluta, soluble proteins (mm-1 of MF), free amino acids (mmol mg-1 of MF), soluble sweetness percentage, total fruit mass (grams) and production of commercial and non-commercial fruit (grams). According to the results, it could be observed that the variation sources carried out significant and exponential effect over high and stemming diameter growth. The increase observed in the accumulated number of lizards of T. absolute, as well as in the percentage of fruits attacked for this plague, confirms the existence of a positive relation enters the doses of Supermagro biofertilizing used and the incidence of this traces. The composition biochemist, relative to the levels of proteins, soluble prolina and sugars in tomateiro leves was modified, increasing in function of the increase of the doses of applied biofertilizing and throughout the cycle of the culture of the tomateiro, cv Saladete. The alterations biochemists if had shown related with the incidence of Tuta absolute in the culture